2006
DOI: 10.1002/ca.20369
|View full text |Cite
|
Sign up to set email alerts
|

Axillary arch in Bulgarian population: Clinical significance of the arches

Abstract: In order to study the incidence of the axillary arch in the Bulgarian population, we examined the axillary regions of 56 formol-carbol fixed human cadavers and observed two cases with a unilateral axillary arch. In the first case, the variant structure was situated on the right side of a 58-year-old female cadaver. The axillary arch extended from the lateral border of the latissimus dorsi to the posterior layer of the pectoralis major tendon. In the second case, the axillary arch was found on the left side of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…In Japanese, the prevalence of axillary arch is found to be 9.1% (8) and 5.3% (9) in two different studies on 176 and 94 body halves respectively. Prevalence of this variation in Turkish population reported as 1.9% in 26 cadavers (3) , where in Bulgarian population reported as 3.6% in 56 cadavers (10) and in Spanish population it is reported as 3% from a study of 50 cadavers (11) . This indicate that incidence of Axillary arch varies in different countries though the incidence is unknown in Indians.…”
Section: Discussionmentioning
confidence: 89%
“…In Japanese, the prevalence of axillary arch is found to be 9.1% (8) and 5.3% (9) in two different studies on 176 and 94 body halves respectively. Prevalence of this variation in Turkish population reported as 1.9% in 26 cadavers (3) , where in Bulgarian population reported as 3.6% in 56 cadavers (10) and in Spanish population it is reported as 3% from a study of 50 cadavers (11) . This indicate that incidence of Axillary arch varies in different countries though the incidence is unknown in Indians.…”
Section: Discussionmentioning
confidence: 89%
“…The prevalence of axillary arch in cadaveric dissection in Japanese, Turkish and Bulgarian populations is 9.1%, 1.9% and 3.6% respectively [5][6][7]. On the other hand, it has been recognized in only 0.25% of patients during axillary surgical procedures [8].…”
Section: Discussionmentioning
confidence: 99%
“…Among the other pathologies that AA brought about, hyperabduction syndrome (Mérida-Velasco et al ;Georgiev et al;Rizk & Harbaugh, 2008) thoracic outlet syndrome (Georgiev et al; Rizk & Harbaugh) shoulder instability syndrome (Petrasek et al, 1997) and thrombosis of upper extremity (Turgut et al, 2005) have been reported. So, during preoperative evaluation for axillary block, the chronic pain of the arm should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The most common variation of axilla is the axillary arch (AA) (Daniels & della Rovere, 2000;Besana-Ciani & Greenall, 2005;Georgiev et al, 2007;Millet et al, 2007). Axillary arch may be an extension of the muscle bundle of latissimus dorsi (Miguel et al, 2001;Mérida-Velasco et al, 2003;Georgiev et al), but may also commence by a tendon at the lateral side of the muscle (Mérida-Velasco et al). Typical AA commences from the anterior (or lateral) edge of latissimus dorsi and by passing over the neurovascular bundle it inserts pectoralis major tendon (Natsis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%